2020
DOI: 10.3390/jfb11020025
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Poly(Methyl Methacrylate) in Management of Bone Loss and Infection in Revision Total Knee Arthroplasty: A Review

Abstract: Poly(methyl methacrylate) (PMMA) is widely used in joint arthroplasty to secure an implant to the host bone. Complications including fracture, bone loss and infection might cause failure of total knee arthroplasty (TKA), resulting in the need for revision total knee arthroplasty (rTKA). The goals of this paper are: (1) to identify the most common complications, outside of sepsis, arising from the application of PMMA following rTKA, (2) to discuss the current applications and drawbacks of employing PMMA in mana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 135 publications
0
25
0
Order By: Relevance
“…PMMA is used for anchoring implants to bone, for fracture fixation, and for management of non-critical bone defects (≤5 mm) [6]. GPCs may be able to overcome some of the limitations (e.g., thermal necrosis, volumetric shrinkage) that currently exist with using PMMA in rTKA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PMMA is used for anchoring implants to bone, for fracture fixation, and for management of non-critical bone defects (≤5 mm) [6]. GPCs may be able to overcome some of the limitations (e.g., thermal necrosis, volumetric shrinkage) that currently exist with using PMMA in rTKA.…”
Section: Discussionmentioning
confidence: 99%
“…While rTKA surgeries comprise a relatively small percentage of all joint replacements (and approximately 7% of all knee replacements [2]), revision surgeries are more complex than primary surgical procedures, resulting in higher inpatient costs (nearly double that of the primary total knee arthroplasty (TKA)), decreased function of the knee, and longer patient recovery time [2]. To manage bone loss in rKTA, surgical implants and techniques such as augments, sleeves, cones, bone grafts, and cementation can be used, depending on the bone defect size, bone quality, and patient's age [3][4][5][6]. The following table reviews each treatment option currently available in rTKA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A polymer interface between harder ceramics or metals used for the acetabulum and femoral head exhibits hard-on-soft coupling, a beneficial phenomenon associated with reduced friction and wear at the interface (Affatato et al, 2018). Another common polymer in TKA/THA is PMMA, also termed bone cement, which is used to affix the femoral stem in the medullary cavity as well as repair small bone defects in revision TKA (Hasandoost et al, 2020). The polyethylenes of Sir John Charnley's era have evolved considerably with innovations in this decade aimed at improving wear resistance, such as antioxidant doping and gamma radiation-induced crosslinking.…”
Section: Polymersmentioning
confidence: 99%
“…ALBC has been widely used for the treatment of infected arthroplasty, and given the increased incidence of this type of infection, a large number of review papers is found in which aspects such as release mechanisms, clinical efficacy, and safety of the ALBC are discussed [13,118,[129][130][131][132][133].…”
Section: Antimicrobial Properties In Acrylic Bone Cementsmentioning
confidence: 99%